Dimensões da liberdade concreta: sobre o vínculo entre a teoria social e a Filosofia do Direito de Hegel (Revista Eletrônica Estudos Hegelianos, 2021)
What follows is an attempt to contribute to the enhancement of the connection between Hegel’s philosophy and contemporary social theory. To begin with, I explore the overall commitment of Hegel’s Science of Logic to the resolution of normative paradoxes inherited from Kantian discussions on concept and action (1). Then I intend to interpret Hegel’s innovative notion of ‘Geist’ by considering its structure which, I argue, is inseparable of Hegel’s own solution to the difficulties concerning normativity (2). Finally, my contribution focuses on some general principles one could derive from Hegel’s concept of ‘ethical life’ on behalf of contemporary discussions on the pragmatist basis for social theory (3).